The geochemical and pore characteristics of a typical marine–continental​ transitional gas shale: A case study of the Permian Shanxi Formation on the eastern margin of the Ordos Basin. (November 2021) - Qiu, Zhen; Song, Dongjun; Zhang, Leifu; Zhang, Qin; Zhao, Qun; Wang, Yuman; Liu, Hanlin; Liu, Dexun; Li, Shuxin; Li, Xingtao
Abstract: The marine–continental transitional Permian Shanxi Formation, which is located on the eastern margin of the Ordos Basin, is expected to be another set of economic gas shale for exploration and development in China. In this study, geochemical methods, low-pressure gas adsorption, high-pressure mercury intrusion, and field emission scanning electron microscopy (FE-SEM) imaging were performed to investigate the pore structure characteristics of the second member of the Permian Shanxi gas shale. The results show that the average TOC content of the shale is 5.90%, the average thermal maturity is 2.22% R o, and these organic-rich shales are enriched in clay minerals. Mesopores are the predominant pore type in these shales, and have slit-like shapes. FE-SEM analysis reveals that the interparticle pores associated with clay minerals are more developed than organic-hosted pores, while a few SEM-invisible micropores may be related to the aromatic structures of kerogen in the shale. Pore development in the studied samples is influenced by the TOC and clay mineral contents. The development of organic-hosted pores in the shale shows obvious differences when compared to representative marine gas shales worldwide, which are ascribed to the differences in kerogen types. Nevertheless, the development of micropores and mesopores in the samples is comparable to that of marine shales, which indicates the presence of qualified space for gas storage in the studied shale. This study will provide crucial theoretical guidance for determining of sweet spots and for the further exploration and development of the transitional shale gas. Highlights: Pore characteristics of the marine–continental transitional Shanxi shale were investigated by various methods. Many SEM-invisible micropores were suggested to be developed in the transitional shale. Pore development of the transitional shale was compared with the typical marine shales.